Desmopressin as an adjuvant to opioids or NSAIDs in treatment of renal colic: a nationwide register‐based study†. (9th September 2015) - Juul, Kristian V.; Schroeder, Marie K.; Rittig, Søren; Nørgaard, Jens Peter
Abstract: Aims: Desmopressin has been reported to be effective as an adjuvant to opioids or NSAIDs in management of pain in renal colic; however real‐life data are lacking on the utilisation of desmopressin in this patient segment. Methods: The Danish National Prescription Registry data‐linked with Danish National Patient Registry during a 3‐year period from 2009 to 2011 was used to study prescriptions for desmopressin in renal colic. Results: We identified 888 desmopressin prescriptions for renal colic, dispensed to 95 patients. The mean treatment period was 159 days, with a large variation up to a maximum of 924 days. Approximately two thirds of patients received dosing instructions to administer the drug 4 times daily to provide 24‐h antidiuretic coverage. Among concomitant opioids and NSAIDs, tramadol and ibuprofen were prescribed most frequently. Antidepressants and diuretics were also widely used. A clear sex difference was seen, with female renal colic patients having three times more prescriptions overall than males, and in particular receiving more antidepressants and psychotropic drugs. A total of 4 (4.2%) of the patients experienced hospital admissions because of hyponatraemia or polydipsia during the 3‐year period. We confirmed a previous case report that nephrolithiasis could be at least an occasional complication of successful therapy of Central Diabetes Insipidus (CDI) with desmopressin, identifying 12 CDI patients in total, or 2.4% of all Danish CDI patients in that period, who were also treated for renal colic. Conclusion: In summary, these real‐life prescription data provide exact epidemiological measures on desmopressin utilisation in renal colic. Copyright © 2015 John Wiley & Sons, Ltd.